Pengaruh Laman Resmi Kementerian Terhadap Reputasi : Studi Asosiatif Program Siinas Pada Kementerian Perindustrian - Christoper, Yoyogi (Prisani Cendekia Institute, 2024)
The Ministry of Industry (Kemenperin) is a governmental institution responsible for developing industries in Indonesia. One of the programs initiated by Kemenperin is the National Industrial Information System (SIINAS), aimed at providing industry-related information to the public. This study aims to analyze the influence of the SIINAS Ministry of Industry webpage on reputation through a regression study of the SIINAS program, using a data collection technique involving questionnaires. The research method employed is quantitative, distributing online questionnaires to respondents who have used or accessed the Ministry of Industry webpage and have an understanding of the SIINAS Program. Regression analysis is used to test the relationship between the independent variable (use of the SIINAS Ministry of Industry webpage) and the dependent variable (reputation). This research is expected to contribute to understanding the influence of government webpages, particularly the SIINAS Ministry of Industry webpage, on public perception of institutional reputation.